Transnationalism and Genealogy - Yang, Philip Q. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Transnationalism and genealogy is an emerging subfield of genealogy which intersects with other fields. The last two to three decades have witnessed a significant growth in this subfield, especially in the areas of transnationalism and family arrangements, transnational marriage, transnational adoption, transnational parenting, and transnational care for elderly parents. However, large gaps remain, especially with regard to the impact of transnationalism on lineage. In filling some lacunas in the current literature, Transnationalism and Genealogy represents an initial attempt to frame the relationship between transnationalism and genealogy. The articles included in this book cover various aspects of transnationalism and genealogy from historical periods until the present, with perspectives from anthropology, sociology, history, and African studies. The topics stretch from transnationalism and the emancipation of black kinship to the transformation of a Chinese immigrant family from traditional to transnational as well as the impact of this transformation on its family relations and lineage, a family history of transnational migration across four nation/city states in four generations, the role of social media platforms (Facebook in particular) in facilitating transnational care chains in the Trinidadian diasporic community, and a comparison between Chinese immigrants in the United States and Singapore in transnational parenting. The introductory essay offers a laconic assessment of the subfield of transnationalism and genealogy.